Ion bombardmente induced allooying as layer by layer promoter in heteroepitaxial growth - Gomez, Liliana Maria (2002)
By means of numerical simulations (Monte Carlo and Molecular Dynamics), we have studied the atomistic mechanisms involved in the growth of Co over Cu(1 1 1). We determined the role of the interface alloying as layer by layer growth promoter, and explored the capability of using direct ion beam deposition to tailoring this alloying. We found that tuning the bombarding kinetic energy we are able of achieving a large grade of interface alloying limiting it, at the same time, to the first couple of layers.